Enhanced Spinal Nociceptin Receptor Expression Develops Morphine Tolerance and Dependence - Hiroshi Ueda; Makoto Inoue; Hiroshi Takeshima; Yoshikazu Iwasawa (2000)
The tolerance and dependence after chronic medication with morphine are thought to be representative models for studying the plasticity, including the remodeling of neuronal networks. To test the hypothesis that changes in neuronal plasticity observed in opioid tolerance or dependence are derived from increased activity of the anti-opioid nociceptin system, the effects of chronic treatments with morphine were examined using nociceptin receptor knock-out (NOR(-/-)) mice and a novel nonpeptidic NOR antagonist, J-113397, which shows a specific and potent NOR antagonist activity in in vitro [(35)S]GTPgammaS binding assay and in vivo peripheral nociception test. The NOR(-/-) mice showed marked resistance to morphine analgesic tolerance without affecting morphine analgesic potency in tail-pinch and tail-flick tests. The NOR(-/-) mice also showed marked attenuation of morphine-induced physical dependence, manifested as naloxone-precipitated withdrawal symptoms after repeated morphine treatments. Similar marked attenuation of morphine tolerance was also observed by single subcutaneous (10 mg/kg) or intrathecal (1 nmol) injection of J-113397, which had been given 60 min before the test in morphine-treated ddY mice. However, the intracerebroventricular injection (up to 3 nmol) did not affect the tolerance. On the other hand, morphine dependence was markedly attenuated by J-113397 that had been subcutaneously given 60 min before naloxone challenge. There was also observed a parallel enhancement of NOR gene expression only in the spinal cord during chronic morphine treatments. Together, these findings suggest that the spinal NOR system develops anti-opioid plasticity observed on morphine tolerance and dependence.